2017
DOI: 10.1016/j.jaci.2016.09.047
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate dehydrogenase has a major role in mast cell function, and its activity is regulated by mitochondrial microphthalmia transcription factor

Abstract: The association of mitochondrial MITF with PDH emerges as an important regulator of mast cell function. Our findings indicate that PDH could arise as a new target for the manipulation of allergic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 39 publications
0
35
0
Order By: Relevance
“…We have previously shown that oxidative phosphorylation (OXPHOS)‐mediated ATP production is essential for mast cell function. Pyruvate dehydrogenase is activated following immunological stimulation of mast cells to produce NADH and FADH2 via the Krebs cycle . These cofactors are necessary for the electron transport chain (ETC), which is positively regulated by mitochondrial signal transducer and activator of transcription 3 (STAT3) during mast cell activation to produce more ATP for the degranulation process …”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that oxidative phosphorylation (OXPHOS)‐mediated ATP production is essential for mast cell function. Pyruvate dehydrogenase is activated following immunological stimulation of mast cells to produce NADH and FADH2 via the Krebs cycle . These cofactors are necessary for the electron transport chain (ETC), which is positively regulated by mitochondrial signal transducer and activator of transcription 3 (STAT3) during mast cell activation to produce more ATP for the degranulation process …”
Section: Introductionmentioning
confidence: 99%
“…Finally, direct inhibition of OXPHOS using rotenone blocked degranulation and lowered IL‐6 production in BMMCs . It is likely that OXPHOS fuelled by glucose oxidation rather than FAO is required for mast cell effector functions, as inhibition of pyruvate dehydrogenase (PDH) with CPI‐613 lowered β‐hexosaminidase release and cytokine production in RBL cells and human cord blood‐derived mast cells , while blockade of FAO using the CTP1a inhibitor etomoxir did not affect mast cell functions . As a whole, these studies suggest that glucose‐fuelled OXPHOS is important for mast cell function.…”
Section: Metabolism Of Cells Involved In the Effector Phase Of Type 2mentioning
confidence: 82%
“…In the same model, blocking the entry of glycolysis‐derived pyruvate into the TCA cycle using CPI‐613 decreased airway resistance, which was associated with a reduction in the release of histamine by mast cells. However, CPI‐613 also promoted the infiltration of eosinophils, macrophages, neutrophils, and lymphocytes into the BAL fluid . Finally, the finding that ILC2s might rely on arginine metabolism for their function sheds interesting new mechanistic light on the long‐appreciated beneficial effects of the arginase inhibitor nor‐NOHA on asthma pathophysiology .…”
Section: Conclusion and Future Perspectivementioning
confidence: 94%
“…Enolase, the ninth enzyme of the glycolytic pathway, has been related with mast cell differentiation, and Chakravarty saw in his studies that treatment with fluoride, an enolase inhibitor, diminished the glucose‐supported histamine release . Moreover, inhibition of pyruvate dehydrogenase (PDH), the clue enzyme for the TCA, inhibits mast cell degranulation and cytokine secretion . These last pieces of evidence indicate a glucose‐depending mast cell function.…”
Section: Metabolism Of Cells At the Tumor Microenvironmentmentioning
confidence: 99%